Podcast comedy and 'Authentic Outsiders': how new media is challenging the owners of industry. Issue 1 (2nd January 2017) - Symons, Alex
ABSTRACT: This article furthers the study of American comedy by examining the emerging relationship between celebrity, podcast and other new media, in the careers of Doug Stanhope, Marc Maron and Louis CK. By studying their creative work, and their celebrity images as evidenced in their press coverage, this article suggests that this new generation of 'outsider' comedians is challenging the power of an American television industry which largely excluded them. Most significantly, this article suggests that through the low-budget, less conspicuously mediated form of the podcast, these comedians have been able to manufacture a perceived 'authentic' celebrity image, differing from that which is historically possible in television or film. By result, these 'authentic outsiders' have created a new niche audience for themselves, contributing towards the current transformation of American comedy – the dominance of the major networks being increasingly challenged by smaller cable and online platforms, which reflect an increasingly fragmented audience.